On sound wave spectra in biaxial nematic crystals - Kovalevsky, М.Y.; Shishkin, А.L. (Вопросы атомной науки и техники, 2001)
On the basis of the Hamiltonian approach dynamics of biaxial nematics surveyed and the deduction of the nonlinear equations of ideal hydrodynamics, taking into account the shape, (disk-shaped and rod-shaped of a molecule) and conformation degree of freedom are given. The densities of additive integrals of motion and relevant fluxes are represented in the terms of a thermodynamic potential. The spectra of linear oscillations in these liquid crystals surveyed. Two branches of ultrasonic oscillations are found and the character of an anisotropy of both velocities of sounds is found out.